Interference of DOACs in different DRVVT assays for diagnosis of lupus anticoagulants. Issue 165 (May 2018) - Flieder, T.; Weiser, M.; Eller, Th.; Dittrich, M.; von Bargen, K.; Alban, S.; Kuhn, J.; Knabbe, C.; Birschmann, I.
Abstract: Objective: Determination of lupus anticoagulants (LA) is an important, but still challenging test in the diagnosis of antiphospholipid syndrome (APS). This is especially the case in patients using one of the direct oral anticoagulants (DOACs). The aim of our study was to examine the influence of these drugs on DRVVT assays from two companies (in each case: screening test, confirming test and calculated ratio) and on aPTT and lupus-sensitive aPTT. Methods: We used plasma samples from healthy volunteers spiked with the DOACs dabigatran, rivaroxaban and apixaban (0, 10, 30, 50, 100 ng/mL) for testing. Furthermore, samples from patients receiving a DOAC were investigated. The plasma concentrations of the DOACs were determined using ultra-performance liquid chromatography/electrospray ionization-tandem mass spectrometry (UPLC-MS/MS). Results: Depending on type and concentration, all the DOACs resulted in pathological values in the DRVVT screening assays. In samples spiked with apixaban, no influence on the DRVVT normalized ratio of the two assays was observed, but 7 to 15% of samples from patients receiving apixaban displayed pathological values. In contrast, up to 71% of dabigatran-spiked samples showed normalized ratio values above the cut-off, whereas there was no influence in the patients' samples. In both spiked and patient samples containing rivaroxaban, the DRVVT assays were influenced. Conclusion: LA diagnostics should, under DOAC therapy, be limited to situations in which time-critical evaluation is warranted. It is crucial to take into account the finding that even samples containing DOAC concentrations below the limit of detection of the drugs may lead to false-positive DRVVT measurements. Highlights: The trustworthiness of LA diagnosis in patients under DOAC therapy is limited. DOACs can lead to false-positive results in DRVVT normalized ratio at trough level or even below the detection limit. Under DOAC therapy, a DRVVT test in the normal range in combination with negative APAcan only be used to exclude an APS.